Phosphorylation of C4 and Non-C4 phosphoenolpyruvate carboxylase from panicum and the kinetic behaviour of phosphorylated and non-phosphorylated PEPC - Dhiya Dalila Zawawi; x; Universiti of Sheffield . Faculty of Science (2019)
The C4 photosynthesis pathway is more efficient than C3 photosynthesis due to the capability of
phosphoenolpyruvate carboxylase (PEPC) that provides a C02 high concentration at Rubisco, thus
reducing the photorespiration rate. PEPC is regulated by internal metabolite with malate or aspartate
as its inhibitors, and glucose-6-phosphate (G-6-P) as its activator. Besides, PEPC also regulated by
reversible phosphorylation by protein kinase known as phosphoenolpyruvate carboxylase kinase
(PEPCK), that leads to an activation of the enzyme by G-6-P and decrease the sensitivity to malate or
aspartate. PEPCK shows a high specificity towards PEPC and the reaction has been reported to be light
controlled, but the details of mechanisms of PEPC phosphorylation are still unknown.

In this study, comparative analysis was performed between phosphorylated PEPCs from C3 Panicum
pygmaeum and C4 Panicum queenslandicum produced either by PEPCK or Protein Kinase A (PKA).
Over-expression of PEPCK with solubility tag NusA had produces soluble protein but in small amounts,
and was insufficient for further analysis. Purifying PEPCK without the NusA tag, was unsuccessful
because it exists as an insoluble protein. Thus, PKA was applied since it is known to phosphorylate
PEPC.

The phosphorylation of PEPC by PKA has been confirmed with fluorescence detection, by combining
Pro-Q Diamond and sYPRO Ruby gel stain in 50S-PAGE gel. The phosphate affinity Phos-Tag" was
performed subsequently to ensure all PEPCs present were fully phosphorylated. Peptides resulting
from the trypsin digestion of Phos-Tag" 50S-PAGE gels were analysed by mass spectrometry to
identify phosphorylation site on PEPC. Two phosphopeptides were detected in the PEPC from P.
queenslandtcurm eee-so: from tire P. pygmaeum enzyme.

Phosphorylation of PEPC changed the pattern of kinetic enzyme activity, as well as the malate and
aspartate sensitivity when compared to the non phosphorylated form. The enzyme activity (Vmax) of
PEPC from the C4 species P. queenslandicum increased once phosphorylated, but this was not
observed in the PEPC from the C3 species P. Pygmaeum. In terms of PEP Km, the phosphorylated P.
queenslandicum PEPC, had a lower Km value when compared to the non phosphorylated one. In the P.
Pygmeaum PEPC, phosphorylation did not change the Km (PEP) value or the specific activity.
Phosphorylation increased the specificity of PEPC to bicarbonate in the enzymes from both P.
queenslandicum and P. pygmaeum at pH 8. Phosphorylated PEPC from P. queenslandicum becomes
less sensitive to malate and aspartate inhibition at limiting PEP. In P. pygmaeum, phosphorylation of
PEPC made it less sensitive to aspartate at limited PEP and to malate at both limited and saturated
PEP.

Together, these results lead to understanding how the phosphorylation influence the catalytic activity
of PEPC in C3 and C4 plant species differently and protect the PEPCs against malate and aspartate
inhibition.
1. Introduction -- 2. Material and methods -- 3. Pepck protein expression, purification and application of nusa tag -- 4. Phosphorylation pf pepc with pepck or protein kinase (pka) -- 5. Kinetic behaviour of phosphorylated and non-phosphorylated pepc -- 6. General discussion nad conclusion
x
Thesis (Degree of Doctor of Philosophy) - University of Sheffield, 2020
Includes bibliographical references (leaves 139-157)
Keywords: x; Universiti of Sheffield -- Faculty of Science -- Dissertations; Dissertations, Academic; Plant Ecology; x